2020
DOI: 10.3389/fnins.2020.00523
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Vagus Nerve Stimulation May Enhance Only Specific Aspects of the Core Executive Functions. A Randomized Crossover Trial

Abstract: Background: Individuals are able to perform goal-directed behaviors thanks to executive functions. According to the neurovisceral integration model, executive functions are upregulated by brain areas such as the prefrontal and cingulate cortices, which are also crucially involved in controlling cardiac vagal activity. An array of neuroimaging studies already showed that these same brain areas are activated by transcutaneous vagus nerve stimulation (tVNS). Despite evidence toward effects of tVNS on specific exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 67 publications
2
50
0
4
Order By: Relevance
“…Similar to reports using iVNS, findings on the modulatory effects of tVNS on vm-HRV measures are heterogeneous. Some studies showed an increase of vm-HRV measures after tVNS (Lamb et al, 2017;Bretherton et al, 2019;Sclocco et al, 2019;Tran et al, 2019), but others showed no effects (Weise et al, 2015;Antonino et al, 2017;De Couck et al, 2017;Burger et al, 2019a,b), or showed a decrease of vm-HRV parameters in individuals with high resting vagal activity (Bretherton et al, 2019) and two other studies during both, active and sham stimulation (Borges et al, 2019(Borges et al, , 2020. A potential limitation of vm-HRV measures as a biomarker for tVNS is that the mechanism influencing vm-HRV (i.e., efferent vagal activation) may differ from the mechanistic target of tVNS (i.e., afferent vagal activation), and little is known about the interrelation of these two vagal pathways, i.e., much is known about cervical vagal feedback loops, but not much is known regarding auricular to cervical loops.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to reports using iVNS, findings on the modulatory effects of tVNS on vm-HRV measures are heterogeneous. Some studies showed an increase of vm-HRV measures after tVNS (Lamb et al, 2017;Bretherton et al, 2019;Sclocco et al, 2019;Tran et al, 2019), but others showed no effects (Weise et al, 2015;Antonino et al, 2017;De Couck et al, 2017;Burger et al, 2019a,b), or showed a decrease of vm-HRV parameters in individuals with high resting vagal activity (Bretherton et al, 2019) and two other studies during both, active and sham stimulation (Borges et al, 2019(Borges et al, , 2020. A potential limitation of vm-HRV measures as a biomarker for tVNS is that the mechanism influencing vm-HRV (i.e., efferent vagal activation) may differ from the mechanistic target of tVNS (i.e., afferent vagal activation), and little is known about the interrelation of these two vagal pathways, i.e., much is known about cervical vagal feedback loops, but not much is known regarding auricular to cervical loops.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…Predominantly, these studies are characterized by short stimulation periods, addressing the immediate effects. Psychological targets have been broad (though not all of them are sensitive to tVNS), including: experimentally induced worry (Burger et al, 2019a ); post-error slowing (Sellaro et al, 2015b ); attention to fearful faces (Verkuil and Burger, 2019 ); associative memory (Jacobs et al, 2015 ) or single-item word memory (Giraudier et al, 2020 ; Mertens et al, 2020 ); extinction of fear responses or fear conditioning (Burger et al, 2016 , 2017 , 2018 , 2019b ; Genheimer et al, 2017 ; Szeska et al, 2020 ); implicit spiritual self-representations (Finisguerra et al, 2019 ); flow experience (Colzato et al, 2018b ); response selection during sequential action (Jongkees et al, 2018 ) or during action cascading processes (Steenbergen et al, 2015 ); the recognition of emotions in faces or bodies (Colzato et al, 2017 ; Sellaro et al, 2018 ; Koenig et al, 2019 ); divergent thinking (Colzato et al, 2018a ); conflict-triggered adjustment of cognitive control (Fischer et al, 2018 ); auditory selective attention (Rufener et al, 2018 ) or visual selective attention (Ventura-Bort et al, 2018 ); inhibitory control (Beste et al, 2016 ; Borges et al, 2020 ); automatic motor inhibition (Keute et al, 2018 ); cognitive flexibility (Borges et al, 2020 ; Tona et al, 2020 ); prosocial behavior (Sellaro et al, 2015a ) and reward sensitivity (Neuser et al, 2019 ).…”
Section: Modes Of Applicationmentioning
confidence: 99%
“…Certainly, smartphone applications can overcome many of the barriers that may have prevented in-person interventions from taking place, such as the current social and travel restrictionsas well associal distancing rules. Of the many methods to enhance CVA (Fatisson and Oswald, 2016;Laborde et al, 2018a), for instance transcutaneous vagus nerve stimulation (Borges et al, 2019(Borges et al, , 2020(Borges et al, , 2021, or meditation with mindfulness training (Garland et al, 2014), SPB offers a simple, easy-to-implement, and beneficial intervention technique with both psychological and physiological outcomes for athletes that can be delivered in lockdown or isolation scenarios.…”
Section: Considerations For Slow-paced Breathing Interventionsmentioning
confidence: 99%
“…Given SPB has been shown to improve both CVA and executive functioning in athletes [ 55 , 57 , 59 ], it appears to be a promising technique for the applied field. Despite the existence of other techniques which stimulate the vagus nerve without requiring the active attention of the individual, such as transcutaneous vagus nerve stimulation [ 98 , 99 , 100 ], the advantage of SPB is that it does not require any device, representing a suitable low-cost, low-technology, and non-pharmacological way to stimulate the vagus nerve.…”
Section: Resultsmentioning
confidence: 99%